2018
DOI: 10.1016/j.ekir.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Hyperkalemia in the United States

Abstract: IntroductionThere are limited data on the cost of hyperkalemia.MethodsThis retrospective analysis of the Truven MarketScan claims database assessed the economic burden of hyperkalemia among selected adult patients with hyperkalemia and matched controls.ResultsA total of 39,626 cases (patients with hyperkalemia) were matched to 39,626 controls (patients without hyperkalemia) based on age, dialysis, chronic kidney disease (CKD) stage, heart failure, and renin-angiotensin aldosterone system inhibitor use. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
63
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 24 publications
1
63
1
Order By: Relevance
“…The management of HK is a major yet unmet need in the Nephrology setting, in spite of the negative impact of this alteration on patient prognosis and the obvious high costs of hospitalization and dialysis [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…The management of HK is a major yet unmet need in the Nephrology setting, in spite of the negative impact of this alteration on patient prognosis and the obvious high costs of hospitalization and dialysis [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…8,9 When considering this future perspective, attaining a cost analysis of HK is preliminary and functional to the best implementation of the new anti-hyperkaliaemic agents. Few studies have evidenced that HK is a costly event; these studies were however based on retrospective analyses in unselected populations either derived from commercial or insurance databases [10][11][12] or from databases covering primary and secondary care. 13 Conversely, it is essential to gain this information in CKD patients under nephrology care for two major reasons: first, these referred CKD patients profoundly differ from general CKD population in terms of prognosis and management [14][15][16][17][18][19] ; second, a larger use of the new K binders is obviously expected in renal clinics that are the reference of care for high-risk CKD patients.…”
mentioning
confidence: 99%
“…Nevertheless, consistent with clinical trial findings, 21 the present study demonstrates that patients continuously exposed to patiromer for 6 months also had high RAASi continuation rates. In an observational study of patients with HK, [26] the 1-year hospital admission and ED visit rates were 0.44 and 0.86, respectively. These were consistent with the baseline (ie, 6 months pre-index) rates in the present study, though substantially higher than the observed hospital admission and ED visit rates following 6 months of CE to patiromer (0.17 admission rate; 0.40 ED rate) and SPS (0.23 admission rate; 0.64 ED rate).…”
Section: Discussionmentioning
confidence: 99%